A54 Creating policy-relevant spatial measures of transport which map to health behaviours and outcomes. Issue 2 (June 2015) - Badland, Hannah; Mavoa, Suzanne; Villanueva, Karen; Roberts, Rebecca; Davern, Melanie; Giles-Corti, Billie
Abstract: Background: Using a health and wellbeing lens, 'liveable' communities are viewed as safe, attractive, socially cohesive and inclusive, and environmentally sustainable, with affordable and diverse housing linked via public transport, walking, and cycling to employment, education, public open space, local shops, health and community services, and leisure and cultural opportunities. The notion of liveability and how best to measure its constructs, has become a key priority for Australian health-sector decision-makers. Yet, until recently, limited systematic research has examined the influence of liveability on health and wellbeing, and how to best to measure liveability within a policy context. Transport is a key component of liveability, with opportunity for evidence-based, replicable, and policy-relevant spatial transport measures to inform planning and support health. Yet, little is known about: which neighbourhood-level spatial transport measures are most useful; at what geographic scales they should be applied; conceptually how they might be related to health behaviours and outcomes; whether indeed, they are related to health and wellbeing outcomes; and how they relate to urban and transport planning policy. As such, we: (1) developed a conceptual model using a social determinants of health lens to identify potential pathways transport might impact health behaviours and outcomes; and then (2) explored the most useful spatial measures for decision-makers to determine how transport supports or hinders health and wellbeing. Methods: Spatial transport measures documented in Australian policy documents, as well as associations shown in the transport, planning, and health academic literature were identified and guided the development of the transport conceptual framework and the final selection of spatial measures. Results: Neighbourhood-level spatial measures were identified and created for each of the 'neighbourhood attributes' identified in the conceptual model. Where possible, these spatial measures aligned with Australian planning policy, and where none existed, were created based on academic literature. In total, 23 spatial transport measures were identified relevant to Victoria, Australia. These were categorised into neighbourhood and household attribute spatial measures including access public transport, car reliance, cycling, and traffic exposure. Conclusions: This work will explore how area-level transport variations determined by policy and planning decisions are associated with population health and inequalities. The next stage is to test different combinations of the spatial transport measures to identify an optimal 'transport' indicator for inclusion in future liveability-related research.